Opening up the black box of a Gateway to Medicine programme : a realist evaluation - Gibson Smith, Kathrine (2021)
A Gateway to Medicine programme, developed in partnership between a further and higher education setting and implemented to increase the socioeconomic diversity of medicine, was examined to identify precisely what works within the programme and why.